Case report: Dual atrioventricular nodal non-reentrant tachycardia with six types of ECG patterns leading to tachycardia-induced cardiomyopathy in a 51-year-old man - Ren, Man-Yi; Zhang, Yong; Zhang, Yu-Jiao; Gao, Mei; Sang, Cai-Hua; Cha, Yong-Mei; Hou, Ying-Long (Frontiers in Cardiovascular Medicine, 2022)
More than three types of ECG manifestations in one patient with dual atrioventricular nodal non-reentrant tachycardia (DAVNNT) are rare. We report a 51-year-old male patient with DAVNNT consisting of six types of ECG patterns leading to tachycardia-induced cardiomyopathy. After radiofrequency ablation of the slow pathway, DAVNNT was eliminated and cardiac function was restored.